Berpikir pseudo mahasiswa PGSD pada operasi bilangan bulat - Hajjah Rafiah; M. Saufi; Siti Aulia; Arifin Riadi (STKIP PGRI Banjarmasin, 2018)
The lack of mastery of mathematical concepts is found in PGSD students, especially in integer matter. This is a serious problem because as a potential teacher, PGSD students must have a correct understanding of a concept. One reason for this lack of mastery of the concept is due to the fragile construction of knowledge. This knowledge construction error can be a pseudo bepikir, that is pseudo wrong and pseudo true. Pseudo is true when the student can answer a problem problem correctly, but the reasoning is wrong. On the contrary, pseudo is wrong when the student answers wrong, but the reasoning is correct. This pseudo-thinking is examined using qualitative research design. The subjects of this research are 24 students of PGSD STKIP PGRI Banjarmasin in the odd semester of academic year 2017/2018. The results showed that most of PGSD students who take the subjects of Mathematics Study of SD I had pseudo thinking on the matter of integer operation. Twenty-one students experienced true pseudo and one student experienced pseudo thinking wrong. These results indicate that PGSD students are able to perform integer operations, but are unable to construct the concept of integer operations well because the process is procedural.